Glioma - Contemporary Diagnostic and Therapeutic Approaches 2019
DOI: 10.5772/intechopen.76205
|View full text |Cite
|
Sign up to set email alerts
|

Diffuse Astrocytoma and Oligodendroglioma: An Integrated Diagnosis and Management

Abstract: For the first time, the WHO classification of brain tumors has introduced molecular parameters in the diagnosis of brain tumors. Together with embryonal tumors, the diffuse gliomas have suffered significant changes in diagnosis, prognosis, and response to treatment. A new concept of "integrated diagnosis" comes to combine the classical diagnosis with the molecular one. While it is still impossible to disregard the histopathological component, according to the new rule ("molecular beats histology") makes molecu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 152 publications
0
3
0
Order By: Relevance
“…However, the first step is to validate if the radiomics is effective in identifying the molecular biomarkers. So in the current study, we try to use radiomics features to initially identify four markers of Ki-67, vimentin, S-100 and CD34, which are histological markers recommended in several gliomas diagnosis [9,10,20,46]. In the Ki-67, S-100, vimentin and CD34 radiomics models established in this study, GLCM and RLM were significant predictive features, their radiomics map showed significantly different distribution in Fig 8. The Ki-67 expression of case i was different from case ii and iii, and the GLCM and RLM also showed differences.…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…However, the first step is to validate if the radiomics is effective in identifying the molecular biomarkers. So in the current study, we try to use radiomics features to initially identify four markers of Ki-67, vimentin, S-100 and CD34, which are histological markers recommended in several gliomas diagnosis [9,10,20,46]. In the Ki-67, S-100, vimentin and CD34 radiomics models established in this study, GLCM and RLM were significant predictive features, their radiomics map showed significantly different distribution in Fig 8. The Ki-67 expression of case i was different from case ii and iii, and the GLCM and RLM also showed differences.…”
Section: Discussionmentioning
confidence: 79%
“…The WHO 2016 classification of CNS tumors also introduces both of the phenotype and the genotype into daily diagnosis and makes it possible to lead a more precise diagnosis of the various entities toward a personalized management of brain tumors. Besides the genomic markers mentioned in the WHO 2016, the concept of molecular diagnosis also promotes immunohistochemical assays to involve more molecular biomarkers besides those for traditional gliomas grading, leading to more precise pathological subtype and better prognostic prediction [9,10]. In recent years, great progress was obtained in the molecular pathology of neuro-tumors and a series of molecular markers have been found to be helpful in the clinical differential diagnosis and prognosis predicting of gliomas, among which Ki-67, vimentin, CD34 and S-100 are four vital biological behavior biomarkers [11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation